A Concise and Sequential Synthetic Approach for Constructing [1,3]oxazino[3,2-a]indolyl chalcones from 2-oxindole - Sathananthan, Kannadasan; Kamaraj, Sanjay (Synlett)
A base-promoted, transition metal-free sequential synthesis of 3,4-dihydro-2H-oxazino[3,2-a]indole-10-carbaldehyde and its chalcone analogues is reported. The fused oxazinoindole framework was efficiently constructed from 2-chloro-1H-indole-3-carbaldehyde and 3-halopropanol through an N-alkylation followed by intramolecular cyclization. Subsequent Claisen–Schmidt condensation of the resulting carbaldehyde with various substituted acetophenone derivatives under basic conditions afforded the corresponding chalcone analogues in good to excellent yields. All the compound were characterised by various spectroscopic techniques.